Long-Term Follow-Up of Lichtenstein Repair of Inguinal Hernia in the Morbid Patients With Self-Gripping Mesh (ProgripTM) - Zhang, Weiyu; Zhao, Yixin; Shao, Xiangyu; Cheng, Tao; Ji, Zhenling; Li, Junsheng (Frontiers in Surgery, 2021)
Objective: This study aimed to demonstrate the safety and the efficacy of the self-gripping mesh (ProgripTM) for inguinal hernia repair in morbid patients of the higher American Society of Anesthesiologists (ASA) classification (ASA III and IV). The incidence of chronic pain, postoperative complications, and hernia recurrence was evaluated. Methods: Data were collected retrospectively from the files of the patient and were analyzed for 198 hernias in 147 patients. All the patients included in this study had undergone inguinal hernia repair by Lichtenstein approach with the self-gripping mesh (ProgripTM) in the same clinical center. Preoperative, perioperative, and postoperative data were collected and a long-term follow-up of 31.8 ± 19.5 m (5–60 m) was performed. Complications, pain scored on a 0–10 numeric rating scale (NRS), and hernia recurrence were assessed. Results: During the past 5 years, 198 hernias in 147 patients were repaired with the Lichtenstein procedure with the self-gripping mesh (ProgripTM). The majority of the patients were high level of the ASA classification (ASA III and IV) (95.9%), with ASA III (10.2%) and IV (85.7%). The mean operation time was 71.2 ± 23.8 min. The mean length of postoperative stay was 2.5 ± 2.1 days. There were no intraoperative complications. About 14 cases (7.1%) suffered from postoperative surgical wound complications, which were limited to the skin and subcutaneous tissue and were cured with the conservative methods successfully; there was no mesh infection, the acute postoperative pain was low or mild [visual analog scale (VAS) score ≤ 4] and the chronic postoperative pain was reported in three patients (1.5%) and tolerable, hernia recurrence (femoral hernia recurrence) occurred in one patient half a year after during the follow-up period. Conclusion: This study demonstrated the advantages of the self-gripping mesh in hernia repair of the high-risk patients with inguinal hernia (ASA III and IV) by Lichtenstein procedure under local anesthesia.